ANALISA PERBEDAAN PERHITUNGAN PPH 21 TERHADAP KARYAWAN TETAP DAN KARYAWAN TIDAK TETAP SERTAPENGARUHNYA TERHADAP KESEJAHTERAAN KARYAWAN - Rachmawati, Susan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Everyone who make money will be taxed namely pph article 21, but not everyone knowing how calculation the tax .so they do not mengetahi whether immensity tax they paid according or not. Hence writers themed about calculation pph 21 against the employee fixed and not fixed and its influence on the welfare of employees. Methods writer use in writing . This are using studies literature and enforcement conclusion of. This research result there are differences in the process of calculation between disclosed does not remain of them: to disclosed fixed production of a month-to-month direct added by allowance the given by a company reduced by spending be a burden disclosed then multiplied 12 to make money net year after that reduced income the result are included in tariff article 17 to get immensity tax a year yes Keywords: permanent employees, the employee is not fixed, the PPh 21